ETNOMATEMATIKA MELAYU: MENGUNGKAP KONSEP MATEMATIKA GEOMETRI PADA TEPAK SIRIH - Annajmi, Annajmi (FKIP Universitas Citra Bangsa, 2024)
Abstract. Mathematics learning carried out in schools currently is still formal and theoretical based on textbooks and is less varied. This has an impact on students' desire to learn mathematics. Thus, there needs to be a relationship between school mathematics and mathematics outside of school. An ethnomathematics approach can be used to connect culture and mathematics. In addition, mathematics that integrates culture will have a significant impact on mathematics lessons. The aim of this research is to gain an understanding of the geometric concepts found in